PREVALENCE AND TYPE OF MICROORGANISMS ISOLATED FROM PHONES USED BY MEDICAL STAFFS/STUDENTS, WORKING/STUDYING IN A TERTIARY CARE CENTER - S., ANUSHA CAROLINE SAROJ; PREETHY, R.; VENNILA, ROSY (International Journal of Current Pharmaceutical Research, 2021)
Objective: To find out the prevalence and type of microorganisms isolated from mobile phones used by health care workers, students working/studying in a tertiary care center as well as to find the rate of contamination of the hands of the individual. Methods: Swabs moistened with sterile saline was used to swab on phone surfaces and was incubated using standard culture and identification methods. The respective user was instructed to imprint their fingers of both hands on plates of culture media. These were incubated and processed as per standard culture methods. Results: The most common isolated microorganisms in both groups were Coagulase-negative Staphylococci (CoNS) and MSSA. Among Mobile phones of HCW, the highest contamination rate was noted in physicians 70% followed by Intensive care doctors 60%, and Nurses. Finger impression growth rate was observed high among Nurses 70% followed by Intensive care doctors 60% and physicians 40%. Conclusion: There is found to be a moderate contamination rate of mobile phones and fingers with pathogenic bacteria as well as normal flora of skin isolated from health care workers. Mobile phones and hands of Health care workers serve as a potential reservoir for hospital-acquired infections as multi-drug resistant pathogenic bacteria. In order to reduce the incidence of nosocomial infections, there should be an implementation of handwashing practices.